ANALISA ELEKTROKOAGULASI AIR ASAM TAMBANG TERHADAP NILAI pH dan KADAR Fe - Ashari, Ashari (JURNAL SURYA ENERGY, 2016)
Most of the Power plant in Indonesia is a steam power plant using coal-fired. Coal demand certainly related tocoal mining activities that will have an impact in the form of the formation of acid mine drainage. it hasundergone a chemical reaction process will have a direct impact on the quality of soil and groundwater due to thepH of groundwater in the area is declining sharply. This condition will affect the levels of Fe dissolved in theground water. The Water has a low pH and high Fe content need to be treated to achieve water quality standardsof waste coal mining activities in accordance with Kep.MENLH No. 113 Appendix I, 2003. Therefore appliedelectrochemical processes in acid mine drainage using electrocoagulation technology to be able to fix the pHvalue and the content of Fe dissolved in the water. From the research that has been done using technologyelektrokoagulai found that the pH value of acid mine drainage can be increased to 53.38% and a decrease Fecontent to 97.35%